BIRDS IN SELECTED FOLK SONGS OF RAJASTHAN - Sharma, Sneha (International Journal of Research -GRANTHAALAYAH, 2020)
Folk songs play a substantial role in the cultural identity of a region. It is an expressive form of customs, traditions and daily life of the common folk which presents a multitude of stories and voices an array of feelings and emotions. Folk songs serve as testimony to the past events of war, community, customs and traditions, rites and rituals. Folk songs also identify and define the region, and help one understand the natural aspects like climate,seasons, topography, agriculture, flora and fauna. The present study focuses on the description and presence of Avifauna imagery and symbolism in Rajasthani folk songs, and the impact of industrialisation and migration resulting in the decline of bird population and folk song traditions.